Trust Evaluation in an Android System for Detection and Alert Falls - Ferreira, Andressa Bezerra; Piva, Leonardo Sabadini; Braga, Reinaldo Bezerra; Andrade, Rossana Maria de Castro (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2014)
The number of people who need special care and are living alone has increased significantly in recent years. To help and assist them, different kinds of systems have been developed, for example, to detect and alert falls. However, the acceptance of such systems requires on the user part the belief that the system uses the collected data properly and not cause any harm. Specifically, trust for ubiquitous systems, which represent computing everywhere, anytime, and transparent for the final user, is a relevant issue. Thus, this paper evaluates, using measures of software quality, trust in a ubiquitous system, called fAlert, for detecting and warning falls. fAlert is an Android system that makes use of sensors to detect anomalies in everyday user activities.